2013
DOI: 10.1155/2013/560417
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid Saponins Isolated fromPlatycodon grandiflorumInhibit Hepatitis C Virus Replication

Abstract: Hepatitis C virus (HCV) infection is a major cause of liver disease, including cirrhosis and hepatocellular carcinoma. Due to significant adverse effects and emergence of resistant strains of currently developed anti-HCV agents, plant extracts have been considered to be potential sources of new bioactive compounds against HCV. The aim of this study was to evaluate the functional effects of triterpenoid saponins contained in the root extract of Platycodon grandiflorum (PG) on viral enzyme activities and replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…It is a well-known medicinal plant in China and other East Asian countries and has been traditionally used as a medicine and food additive for various respiratory diseases, including bronchitis, asthma, tonsillitis, pulmonary tuberculosis and other inflammatory diseases ( Takagi and Lee, 1972 ; Kim et al, 1995 ; Shin and Lee, 2002 ). Oleanane-type triterpenoid saponins are the main chemical components of P. grandiflorum , mainly including platycodin D, D2, D3, deapioplatycodin D, D2, polygalacin D and platyconic acid A ( Kim J.W. et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-known medicinal plant in China and other East Asian countries and has been traditionally used as a medicine and food additive for various respiratory diseases, including bronchitis, asthma, tonsillitis, pulmonary tuberculosis and other inflammatory diseases ( Takagi and Lee, 1972 ; Kim et al, 1995 ; Shin and Lee, 2002 ). Oleanane-type triterpenoid saponins are the main chemical components of P. grandiflorum , mainly including platycodin D, D2, D3, deapioplatycodin D, D2, polygalacin D and platyconic acid A ( Kim J.W. et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Platycodin D was also spermicidal, contraceptive (Lu et al, 2013 ), and anti-atherosclerotic (Wu et al, 2012 ). It has also been reported that platycodin D could be an alternative treatment of obesity by down-regulating lipid accumulation (Lee et al, 2012 ) and that platycodin D was identified as active component with anti-HCV activity (Kim et al, 2013 ). However, there was no report on the anti- M. pneumoniae property of Platycodin D.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur fumigation was reported to be able to cause chemical changes in herbs [ 16 , 17 ]. In this study, chemical changes were observed in Jiegeng subjected to sulfur fumigation.…”
Section: Resultsmentioning
confidence: 99%
“…Significant decrease and/or loss of these glycosides caused by sulfur fumigation may negatively affect the bioactivities of Jiegeng . It has been reported that platycodin D, platycodin D 2 and platycodin D 3 have anti-HCV activity [ 17 ]; platycodin D is a potent adjuvant of specific cellular and humoral immune responses against recombinant hepatitis B antigen [ 13 ], and can reduce pancreatic lipase activity significantly [ 18 ]. Whether the decrease in contents of these glycosides during sulfur fumigation will reduce the above mentioned bioactivities of Jiegeng remains to be explored.…”
Section: Discussionmentioning
confidence: 99%